Scientific research paradigms - Ramos, Carlos Alberto (2015)
Positivism, post-positivism, critical theory and constructivism are the paradigms that support scientific research. It is important for a researcher knows which of them is positioned for being a clear conception of the reality of phenomenon under study. In this article a review is made of these philosophical foundations and analyzes under the two classical approaches to scientific research: quantitative and qualitative. In conclusion the proper characterization of each paradigm is stated in the ontological, epistemological and methodological conception in the scientific research process.